Blue Nevus Involving Minor Salivary Gland. Issue 1 (January 2022) - Alramadhan, Saja A.; Ruddocks, Lauren A.; Bhattacharyya, Indraneel; Cohen, Donald M.; Islam, Mohammed N.
Abstract : Abstract: Blue nevus is a benign melanocytic tumor that commonly occurs on the skin. It appears as a solitary, well-demarcated, dark blue nodule or smooth-surfaced macule. Blue nevus has been reported in the lymph nodes, parotid, and prostate glands. In the oral cavity, blue nevus accounts for one-third of all oral mucosal melanocytic nevi, with the palate being the most common location. Microscopically, the blue nevus is composed of a benign proliferation of bipolar dendritic melanocytes in the deeper layers of the connective tissue. The distinctive blue hue is attributed to the deep location of the melanocytes and the Tyndall effect. To our knowledge, this is the first article to document blue nevus involving minor salivary glands. One month following the excisional biopsy and thereafter, no evidence of recurrence was noted. The diagnosis was established only after histopathological examination of the biopsy specimen. Microscopic examination of oral pigmented lesions is necessary for a conclusive diagnosis and to rule out neoplasms such as melanoma that can clinically mimic blue nevus.